Digital Documentation in Narrow Burial Spaces Using a 360° Borescope Prototype - Riccardo Valente; Luigi Barazzetti; Mattia Previtali; Fabio Roncoroni (Heritage, 2023)
This paper illustrates and discusses a novel method for the digital documentation of human remains in narrow spaces. A 360° borescope prototype made up of a panoramic camera and a lighting LED system was designed and assembled to acquire data in confined spaces for photogrammetric processing. A series of laboratory experiments were planned to assess the method’s validity. A modern concrete tunnel and a mock grave were surveyed using surveying instruments and a laser scanner, comparing the results with the borescope prototype. Then, data acquisition was moved to the field, i.e., in a real case study. Two burial vaults in a church containing human remains were selected and surveyed. The remains were accessible only from small breaches. The results show that using the 360° borescope is suitable for documenting narrow/confined spaces with minimum alteration of the scene. This result can be of interest for archaeological and forensic purposes, especially when the context is hardly accessible, with minimal intervention on the scene.